Testing the Galileo High Accuracy Service User Terminal (HAUT) in Static Scenarios - Emilio González; Pedro Pintor; Ana Senado; Narayan Dhital; Javier Ostolaza; Carmelo Hernández; Juan Vázquez; Javier de Blas; Stefano Lagrasta (Engineering Proceedings, 2023)
In just one year, Spaceopal and its partners developed the Galileo HAS Performance Characterization User Algorithm for the EU Agency for the Space Programme (EUSPA). The Galileo HAS User Terminal (HAUT) hosts the Galileo HAS Performance Characterization User Algorithm. The Galileo HAS User Terminal is a portable, configurable and autonomous device powered by a triple-frequency Galileo and GPS receiver and calculates a single- (Galileo) or multi-constellation (Galileo + GPS) Galileo HAS and Open Service (OS) positioning, velocity and time (PVT) solution. The User Terminal can be configured to retrieve Galileo HAS corrections either from Galileo Signal-in-Space (SIS) over E6-B or Internet Data Distribution (IDD) over NTRIP in an RTCM3 format and works in different frequency combinations that can be configured by the user. The User Terminal is a robust device (IP64) with multiple communication and logging capabilities. The Galileo HAS Initial Service was declared on 24 January by the European Commission, and provides free-of-charge, high-accuracy Precise Point Positioning (PPP) corrections (orbits, clocks) and code biases for Galileo and GPS to achieve real-time improved user positioning performance. The Galileo HAS Service Definition Document (SDD) and the HAS SIS Interface Control Document (HAS SIS ICD) are freely available to users on the web portal of the European GNSS Service Centre and HAS Internet Data Distribution Interface Control Documents (HAS IDD ICD) are available after registration. Using the Galileo HAS User Terminal, this article presents the results of Galileo HAS User Terminal’s performance, configuring the User Algorithm to assume static dynamics. It is to be noted that this configuration provides a significant performance benefit with respect to a configuration compatible with kinematic operation. Preliminary results indicate the Galileo HAS User Terminal achieves excellent accuracy.